(untitled) (المجلة العربية للعلوم و نشر الأبحاث, 2021)
This research aimed to identify some of Al-Zamlkani’s responses and evaluate them according to the experts of linguistics using the descriptive and analytical method. This was achieved with a presentation of a brief translation of Al-Zamlkani; as the research centered on collecting the scholar’s responses in his explanation in the nouns’ chapters and his genres and grammatical aspects in more than one chapter. This includes a response to an Absolute Had (limit) that needed a restriction, or certain expressions that confuse the scholar; thus, where incorrectly studied. As for his response to Ibn al-Hajib in the chapter related to his personal perspectives presented in this explanation, he opposed him on the one aspect; while defended what Al-Zamakhshari mentioned about some of them in other chapters. These issues were presented in two topics: The first was Al-Zamlkani’s responses to Al-Zamakhshari and Ibn al-Hajib in the nouns’ categories; while the second was Al-Zamlkani’s responses to al-Zamakhshari and Ibn al-Hajib in the aspects of noun parsing. The most important results demonstrated by the research were that Al-Zamlkani was seeking to facilitate the language and clarify the grammatical issues; as his responses varied when discussing Al-Zamakhshari; including a response to an Absolute Had that required restriction or expressions that confuse the scholar; thus, where incorrectly studied. Al-Zamlkani also dealt with chapters of certain grammatical aspects; where his responses showed reliance on the logical aspect and philosophical thought at times and on his sheik and teacher Ibn al-Hajib’s belief at other times by quoting what was explicitly or implicitly mentioned. The lack of interpretation and clarification in some of Al-Zamakhshari’s phrases is a reason for the confusion that does not have a meaning for the scholars, including Al-Zamlkani.